The Effect of Specific Excise Taxes on the Output of the Individual Multiproduct Firm - Wise, J. (Review of Economic Studies, 1962)
Journal Article The Effect of Specific Excise Taxes on the Output of the Individual Multiproduct Firm Get access J. Wise J. Wise Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 4, October 1962, Pages 324–326, https://doi.org/10.2307/2296308 Published: 01 October 1962